Genetic Studied of Heterosis and Heterobeltiosis in F1 Hybrids of Upland Cotton for Yield and Fibre Traits: Genetic Study of F1 Hybrids in Cotton (Biological Sciences - PJSIR, 2026)
The mean performance of parents and hybrids is highly significant for all the traits. The hybridsMNH-886 x BT-703 possess maximum numbers of bolls formed 90 days after planting, plant height andthe number of sympodial branches/plant, while CRIS-134 x MS-370 produced a maximum number ofbolls/plant. Moreover, the high ginning out turn % and seed yield/plant were reported by the cross ofBT-703 x MS-370. The cross MNH-886 x IR-1524 gave the highest seed index with the longest staplelength. The cross MNH-886 x BT-703 for bolls formed at 90 days after planting, plant height, sympodialbranches/plants, number of bolls/plant, seed index and seed cotton yield/plant, while CRIS-134 x IR-1524high relative heterosis and heterobeltosis boll weight; BT-703 x MS-370 and expressed highest ginningout turn%, MNH-886 x IR-1524 can be utilized for the future breeding program for important yieldcontributing traits.